Pyoderma Profile In The Dermato-Venereology Outpatient Unit Of Aisyiyah Islamic Hospital Malang On January-December 2017 - Sri Adila Nurainiwati; Mira Mira (Saintika Medika, 2020)
Background:Pyoderma is a skin infection caused by gram-positive bacteria such as Staphylococcus, Streptococcus, or both, which are still one of the main problems causing high morbidity rates, especially in developing countries and tropical climates, including Indonesia.Objective: To find out the pattern of pyoderma in the outpatients from Dermatovenereology unit of AisyiyahIslamic Hispital on January-December 2017.Methods: This retrospective study extracted data from the medical records of Dermatovenereology outpatient unit of AisyiyahIslamic Hospital in the January-December 2017 time frame.Results: The incidence of pyoderma at Aisyiyah Islamic Hospital in Malang during 2017 was 46 cases (11.03%). The incidence of pyoderma is higher in males (56.52%) and according to age, the most affected age group is 0-11 years (39%). The most common level of education is SMA/MA (high school), which is 34.78%. Most types of pyoderma are impetigo (32.6%). The most used systemic antibiotic therapy is cefixime at 35.71% and the most used topical therapy is mupirocin (42.86%).Conclusion: The most impetigo type of pyoderma, males, with the most age group is 0-11 years, high school education level, the most used systemic therapy is cefixime and the most used topical therapy is mupirocin.